Towards Inclusive Financial Services: The Responsibility Of Financial Sector Business Actors In Providing Disability-Friendly Services - Davina Azzahra Aldien; Rouli Anita Velentina (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the responsibility of financial sector business actors (PUSK) in providing inclusive financial services for persons with disabilities. The main focus of this study is the SETARA Guidelines on Accessible Financial Services for Empowered Persons with Disabilities, issued by the Financial Services Authority (OJK) as a reference. The method used is normative juridical with a regulatory approach, through a literature study of laws, regulations, and related policy documents, including Law Number 8 of 2016 concerning Persons with Disabilities. The study’s results show that the SETARA Guidelines have comprehensively formulated accessibility principles across six service aspects: physical infrastructure, digital infrastructure, service sensitivity, document accessibility, complaint mechanisms, and assistance. However, the implementation of these guidelines still depends on the commitment of each PUSK. This may potentially create access gaps for consumers with disabilities and does not yet guarantee the fulfillment of their rights to equal financial services. The study recommends integrating the principles of the SETARA Guidelines into mandatory regulations and strengthening the role of the OJK in compliance supervision. These efforts are necessary as part of the transformation towards an inclusive and equitable national financial system.